2017
DOI: 10.1159/000481101
|View full text |Cite
|
Sign up to set email alerts
|

Repair of an Autologous Saphenous Vein Graft Aneurysm Ten Years after Renal Artery Reconstruction during Live Donor Renal Transplantation

Abstract: Saphenous vein graft (SVG) aneurysms (SVGA) after renal transplantation represents a rare vascular complication with subsequent challenging multidisciplinary treatment. We present a case of a 30-year-old female who received a live donor kidney transplantation for end-stage renal disease that was caused due to the hemolytic uremic syndrome. Postoperatively, an insufficient graft perfusion due to an arterial kinking was noted and repaired using an autologous SVG interposition. Ten years later, a 3-cm aneurysm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Previous studies with autologous saphenous vein transplant renal artery reconstruction have demonstrated concerns with late complications such as pseudoaneurysm formation and stenosis. [35][36][37] However, we have shown cryopreserved saphenous vein to be a potentially suitable alternative to saphenous vein autograft, prosthetic, or other conduits in the mid-term. Future studies are needed to determine the utility and safety of cryopreserved vessel allograft for long-term transplant vessel reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with autologous saphenous vein transplant renal artery reconstruction have demonstrated concerns with late complications such as pseudoaneurysm formation and stenosis. [35][36][37] However, we have shown cryopreserved saphenous vein to be a potentially suitable alternative to saphenous vein autograft, prosthetic, or other conduits in the mid-term. Future studies are needed to determine the utility and safety of cryopreserved vessel allograft for long-term transplant vessel reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is a commonly used autologous graft for various vascular reconstruction. Although there are some reports on delayed saphenous vein graft aneurysms [4], the saphenous vein's caliber, length, ease of exploration and little venous drainage consequences when sacri ced has made it a versatile autologous graft. [4] A midline laparotomy was performed for direct access to the anteriorly placed aneurysm and iliac vessels.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Although there are some reports on delayed saphenous vein graft aneurysms [4], the saphenous vein's caliber, length, ease of exploration and little venous drainage consequences when sacri ced has made it a versatile autologous graft. [4] A midline laparotomy was performed for direct access to the anteriorly placed aneurysm and iliac vessels. A midline transperitoneal approach provided direct access to the renal transplant graft hilum and TRAA.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…It is a commonly used autologous graft for various vascular reconstruction. Although there are some reports on delayed saphenous vein graft aneurysms [ 3 ], the saphenous vein’s caliber, length, ease of exploration and little venous drainage consequences when sacrificed has made it a versatile autologous graft [ 3 ].…”
Section: Therapeutic Interventionmentioning
confidence: 99%